Effects of time of day on pacing in a 4-km time trial in trained cyclists - Zadow, E. K.; Fell, J. W.; Kitic, C. M.; Han, J.; Wu, S. S. X. (International Journal of Sports Physiology and Performance, 2020)
Context: Time of day has been shown to impact athletic performance, with improved performance observed in the late afternoon-early evening. Diurnal variations in physiological factors may contribute to variations in pacing selection; however, research investigating time-of-day influence on pacing is limited. Purpose: To investigate the influence of time-of-day on pacing selection in a 4-km cycling time trial (TT). Methods: Nineteen trained male cyclists (mean [SD] age 39.0 [10.7] y, height 1.8 [0.1] m, body mass 78.0 [9.4] kg, VO2max 62.1 [8.7] mL·kg-1·min-1) completed a 4-km TT on 5 separate occasions at 08:30, 11:30, 14:30, 17:30, and 20:30. All TTs were completed in a randomized order, separated by a minimum of 2 d and maximum of 7 d. Results: No time-of-day effects were observed in pacing as demonstrated by similar power outputs over 0.5-km intervals (P = .78) or overall mean power output (333.0 [38.9], 339.8 [37.2], 335.5 [31.2], 336.7 [35.2], and 334.9 [35.7] W; P = .45) when TTs were performed at 08:30, 11:30, 14:30, 17:30, and 20:30. Preexercise tympanic temperature demonstrated a time-of-day effect (P < .001), with tympanic temperature higher at 14:30 and 17:30 than at 08:30 and 11:30. Conclusion: While a biological rhythm was present in tympanic temperature, pacing selection and performance when completing a 4-km cycling TT were not influenced by time of day. The findings suggest that well-trained cyclists can maintain a robust pacing strategy for a 4-km TT regardless of time of the day.